English language learning materials : a critical review - Tomlinson, Brian, 1943- (Continuum, 2008)
This research collection presents a critical review of the materials used for learning English around the world. The first sectionïncludes a discussion of materials for specific learners and purposes, such as young learners, self-study, academic writing and general proficiency. The second section presents a detailed study of the materials used inËurope, Asia, North America, South America, Africa and Australia, and critically evaluates their effectiveness inẗhe teaching of English to speakers of other languages. Taking both the teacher's and the learner's needs into considerat.